Analysis of Short-Term Efficacy of Gasless Single-Port Laparoscopic Inguinal Lymphadenectomy Through Vulva Incision for Vulvar Cancer - Ding, Jin; Teng, Piaopiao; Guan, Xiaoming; Luo, Yonghong; Ding, Huafeng; Shi, Suhua; Zhou, Xiufen; Ni, Guantai (Frontiers in Surgery, 2022)
Objective To investigate the feasibility and short-term efficacy of gasless single-port laparoscopic inguinal lymphadenectomy through vulva incision (VEIL-V). Methods The data of 9 patients diagnosed as vulvar squamous cell carcinoma who underwent single-port laparoscopic inguinal lymph node dissection through vulvectomy incision were retrospectively analyzed. And 13 patients who underwent laparoscopic inguinal lymph node dissection through lower abdominal subcutaneous approach as the control group (VEIL-H). The operation time, blood loss, numbers of unilateral lymph nodes, hospitalization time, and complications between the two groups were compared. Results The operation time of VEIL-V was 56.11 ± 5.94 min, which were shorter than that of VEIL-H (74.62 ± 5.50 min; P = 0.013). Bleeding amount in the VEIL-H was 29.44 ± 2.56, which was significantly lower than that of the VEIL-H group (43.08 ± 4.14 ml; P = 0.021). In the two groups, the numbers of unilateral lymph nodes harvested were similar. The differences in the postoperative hospital stay, skin, and lymphatic complications were not statistically significant. Conclusion Compared with VEIL-H, gasless single-port laparoscopic inguinal lymphadenectomy through vulva incision reduces the difficulty of operation with shorter operation time, and less blood loss, which can be a safe and mini-invasive surgical approach.